2015
DOI: 10.1016/j.jphys.2015.02.017
|View full text |Cite
|
Sign up to set email alerts
|

After-hours or weekend rehabilitation improves outcomes and increases physical activity but does not affect length of stay: a systematic review

Abstract: PROSPERO CRD42014007648. [Scrivener K, Jones T, Schurr K, Graham PL, Dean CM (2015) After-hours or weekend rehabilitation improves outcomes and increases physical activity but does not affect length of stay: a systematic review.Journal of Physiotherapy61: 61-67].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Previous reports have identified the importance of weekend rehabilitation services, and a meta‐analysis showed moderate evidence for shortened duration of hospital stay in stroke patients after additional weekend rehabilitation therapy . Furthermore, a systematic review described increased physical activity and possible improved activities of daily living with added after‐hours rehabilitation . To our knowledge, the present study is the first to investigate the association between weekend rehabilitation and favorable functional recovery and shortened duration of hospital stay in hip fracture patients.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Previous reports have identified the importance of weekend rehabilitation services, and a meta‐analysis showed moderate evidence for shortened duration of hospital stay in stroke patients after additional weekend rehabilitation therapy . Furthermore, a systematic review described increased physical activity and possible improved activities of daily living with added after‐hours rehabilitation . To our knowledge, the present study is the first to investigate the association between weekend rehabilitation and favorable functional recovery and shortened duration of hospital stay in hip fracture patients.…”
Section: Discussionmentioning
confidence: 55%
“…9 Furthermore, a systematic review described increased physical activity and possible improved activities of daily living with added after-hours rehabilitation. 15 To our knowledge, the present study is the first to investigate the association between weekend rehabilitation and favorable functional recovery and shortened duration of hospital stay in hip fracture patients.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Studies have shown that providing additional therapy to stroke survivors during the weekend resulted in improved functional outcomes (Caruana et al, 2017;Kinoshita et al, 2017;Peiris et al, 2013). A small systematic review (n=7 studies) exploring the effect of after-hours rehabilitation (therapy provided on evenings and/ or weekends) showed that additional therapy during after-hours resulted in higher physical activity levels and may improve activities of daily function (Scrivener et al, 2015). However, providing therapy during after-hours and weekends involves additional staffing cost in Australia, as evening or weekend shift allowance makes staffing expenditure expensive.…”
Section: Interventions To Increase Activitymentioning
confidence: 99%